2020
DOI: 10.1186/s13731-020-00125-5
|View full text |Cite
|
Sign up to set email alerts
|

The study of the causal relationship between innovativeness and entrepreneurial intention among undergraduate students

Abstract: In recent years, entrepreneurs have become key drivers of business growth worldwide, since that time, entrepreneurial education has subsequently been garnering an increased level of interest. Entrepreneurship is considered to be a combination of both art and science, used to create value when targeting customers; however, there appears to be a myth when it comes to the recipe required for success. It was discovered by The Office of Small and Medium Enterprise Promotion that less than 10% of Thai small and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 15 publications
6
63
2
4
Order By: Relevance
“…Among undergraduate students, Chaudhary (2017) and Nasip et al (2017) found that innovativeness is positively related to entrepreneurial intentions. The study of Wathanakom et al (2020) found that innovativeness is the highest predictor of entrepreneurial intentions among undergraduate students. These studies indicate that innovativeness will predict entrepreneurial intentions among students.…”
Section: Innovativeness and Entrepreneurial Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among undergraduate students, Chaudhary (2017) and Nasip et al (2017) found that innovativeness is positively related to entrepreneurial intentions. The study of Wathanakom et al (2020) found that innovativeness is the highest predictor of entrepreneurial intentions among undergraduate students. These studies indicate that innovativeness will predict entrepreneurial intentions among students.…”
Section: Innovativeness and Entrepreneurial Intentionsmentioning
confidence: 99%
“…The competitive landscape demands that entrepreneurs offer something new in the form of products, new methods, and processes to take advantage of customers' unmet needs and wants. Wathanakom et al (2020) acknowledge that entrepreneurial educational programmes must emphasise innovativeness, as this skill is important in building entrepreneurial intentions.…”
Section: Theoretical and Policy Implications Of The Studymentioning
confidence: 99%
“…Research Trends in the Measurement of Entrepreneurial Education: A Bibliographic Coupling… DOI: http://dx.doi.org/10.5772/intechopen.96821 the paper by Puni et al [25] highlights that the acquisition of knowledge about entrepreneurship and the recognition of opportunities favour the entrepreneurial intention. Wathanakom et al [8] analyse innovation as a critical factor in the entrepreneurial intention of university students. Also, the authors Vanevenhoven and Liguori [34] present the structure of a longitudinal study that measures the factors associated with entrepreneurial intention in students from 70 countries and 400 world universities.…”
Section: Cluster 6: Drivers Of Entrepreneurial Intentionmentioning
confidence: 99%
“…In this regard, a growing number of research confirms that education plays an important role in promoting entrepreneurship [7,10]. Indeed, entrepreneurial education has been gaining greater interest in literature [8] because it strengthens the entrepreneurial intention [11][12][13][14], favours the acquisition of new skills to compete in the labour market [15], develop a culture of innovation [8,16] and influence positively entrepreneurial self-efficacy in students [17]. Thus, to promote successful entrepreneurship it is necessary to strengthen business education and the entrepreneurial ecosystem [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation